National critical infrastructure and the Polish railway system - Ozog, Berenika (2012)
The purpose of this study was to discuss different approaches and sources of information about national critical infrastructure. Moreover, the Polish railway system was examined in this context in order to provide recommendations for particular critical elements of its infrastructure and suggest actions on how to protect it.